2011
DOI: 10.1155/2011/632870
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Ovarian Cancer Risk due to Prevalence ofBRCA1andBRCA2Variants in Pakistani Population: A Pakistani Database Report

Abstract: Introduction. Pakistani population has a very rich anthrogeneological background with waves of migration from neighboring regions. Incidence rates of breast and ovarian cancer in Pakistan are on such a rapid rise that it is necessary to check the contributory factors, genetic and nongenetic. An insight into the prevalence data emphasizes the formulation of a BRCA1 and BRCA2 database for the Pakistani population. Method. In this study conducted by authors, data from diagnosed cases of both sporadic and inherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
0
24
1
Order By: Relevance
“…These observations suggest that 1014DelGT might be a common mutation in the Muslim community and might have migrated to the Indian population through a pool of Muslim immigrants (Liede et al, 2009). In North-Eastern region, the mutation of 3889DelAG is higher than the rest of the mutation found (Figure 1f), out of nine, three have the family history and found scattered in studied population; it also found in various populations of the world (Thirthagiri et al, 2008;Farooq et al, 2011). The location of 3889AG is towards the C terminus of BRCA1, within the transcriptional activation domain, a region as well reported to interact with the BRCA2 protein, which plays an important role in double stranded break (DSB) repair (Roy et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…These observations suggest that 1014DelGT might be a common mutation in the Muslim community and might have migrated to the Indian population through a pool of Muslim immigrants (Liede et al, 2009). In North-Eastern region, the mutation of 3889DelAG is higher than the rest of the mutation found (Figure 1f), out of nine, three have the family history and found scattered in studied population; it also found in various populations of the world (Thirthagiri et al, 2008;Farooq et al, 2011). The location of 3889AG is towards the C terminus of BRCA1, within the transcriptional activation domain, a region as well reported to interact with the BRCA2 protein, which plays an important role in double stranded break (DSB) repair (Roy et al, 2012).…”
Section: Discussionmentioning
confidence: 72%
“…They then estimate the Percentage involvement of these genes. Nine percent of these cancers show alterations in BRCA1 gene while 3 percent have shown BRCA2 variants while the remaining 88 percent of breast and ovarian cancers can be due to the involvement of other genes (Farooq et al, 2011).…”
Section: Risk Factors Of Breast Cancer In Pakistanmentioning
confidence: 99%
“…The results suggested that a wide range of germline PTEN mutations may play a role in the pathogenesis of breast cancer and may vary in different populations. Farooq et al (2011) emphasized on the formulation of a BRCA1 and BRCA2 database for the Pakistani population (Farooq et al, 2011). Data of mutational screening of the these genes exons along with the results of the previous Pakistani studies for both BRCA1 andBRCA2 genes were summed up to prepare a Pakistani database.…”
Section: Genetic Etiology Of Breast Cancermentioning
confidence: 99%